Espressioni Letterali

  • Materia: Espressioni Letterali
  • Visto: 5418
  • Data: 30/12/2008
  • Di: Redazione StudentVille.it

$-[-(-3/2x^2y^2)(3/2xyz)+(-1/3x^4y^4z):(5/6xy)]((10)/(37)xz)-...$

esercizio svolto o teoria

A cura di: Francesco Speciale

Svolgimento:
$-[-(-3/2x^2y^2)(3/2xyz)+(-1/3x^4y^4z):(5/6xy)]((10)/(37)xz)-(-5/8x^8y^3z^2):(5/4x^4)=$
$=-[-(-9/4x^3y^3z)-2/5x^3y^3z]((10)/(37)xz)+1/2x^4y^3z^2=$
$=-[9/4x^3y^3z-2/5x^3y^3z]((10)/(37)xz)+1/2x^4y^3z^2=$
$=-[((45-8)/(20))x^3y^3z]((10)/(37)xz)+1/2x^4y^3z^2=$
$=(-(37)/(20)x^3y^3z)((10)/(37)xz)+1/2x^4y^3z^2=-1/2x^4y^3z^2+1/2x^4y^3z^2=0$.